Impact of Good Corporate Governance Mechanisms on Financial Performance: Evidence from Indonesian Manufacturing Companies: Dampak Mekanisme Tata Kelola Perusahaan yang Baik terhadap Kinerja Keuangan: Bukti dari Perusahaan Manufaktur Indonesia - Satria, Hendy; As Sahara, Masyitah; Fitriani, Yeni (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates the effect of four independent variables, namely independent commissioners, audit committees, leverage, and firm size, as mechanisms of good corporate governance on the financial performance of Indonesian manufacturing companies. The population consists of 142 companies listed on the Indonesia Stock Exchange (IDX) and publishing financial reports from 2019 to 2022. Panel data regression analysis using E-Views Software is employed for analysis. The findings reveal that independent commissioners, audit committees, leverage, and firm size collectively influence financial performance by 36.2%, with the remaining 64.8% attributed to other factors. All variables demonstrate a significant influence, but only independent commissioners exhibit a negative effect. These findings emphasize the importance of effective corporate governance practices in enhancing financial performance and provide valuable insights for policymakers and stakeholders to foster sustainable and resilient corporate environments. Highlight: Multiple Independent Variables: The study examines the impact of four crucial corporate governance mechanisms, including independent commissioners, audit committees, leverage, and firm size, on the financial performance of Indonesian manufacturing companies. Collective Influence on Financial Performance: The findings suggest that these corporate governance mechanisms collectively contribute to 36.2% of the financial performance variation, highlighting their significant role in shaping company outcomes. Negative Effect of Independent Commissioners: Interestingly, the study reveals that while all variables show a substantial influence, independent commissioners have a negative effect on financial performance, necessitating further investigation and potential policy adjustments. Keyword: Corporate Governance, Financial Performance, Manufacturing Companies, Panel Data Regression, Indonesia